2012
DOI: 10.1186/1751-0759-6-6
|View full text |Cite
|
Sign up to set email alerts
|

Psychosomatic problems and countermeasures in Japanese children and adolescents

Abstract: In Japan there are a number of children and adolescents with emotion-related disorders including psychosomatic diseases (orthostatic dysregulation, anorexia nervosa, recurrent pains), behavior problems and school absenteeism. According to our previous report, the Japanese children had significantly higher score of physical symptoms and psychiatric complaints than did the Swedish children, and these were more strongly influenced by school-related stress than by home-related stress. To enforce countermeasures fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 17 publications
2
26
0
2
Order By: Relevance
“…The present study reveals that students would benefit from these activities, especially male students and students in lower secondary schools. Moreover, as young people struggle with their mental health some issues might be of even greater importance, such as positive school factors; reduced competition, comparisons and requirements; more supportive relations with teachers and peers; and a feeling of security, all of which are related to fewer subjective health problems (Tanaka, Terashima, Borres, & Thulesius, 2012). Further, students are exposed to different classrooms with higher-to lower-quality interactions.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…The present study reveals that students would benefit from these activities, especially male students and students in lower secondary schools. Moreover, as young people struggle with their mental health some issues might be of even greater importance, such as positive school factors; reduced competition, comparisons and requirements; more supportive relations with teachers and peers; and a feeling of security, all of which are related to fewer subjective health problems (Tanaka, Terashima, Borres, & Thulesius, 2012). Further, students are exposed to different classrooms with higher-to lower-quality interactions.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…A national survey reported that 6% of children 10-15 years old suffer from orthostatic intolerance in Japan. 9 In the screening survey from the present study, 59% of patients had symptoms suggestive of orthostatic intolerance. Although our study is not directly comparable to the aforementioned survey because of the difference in backgrounds of the populations and the effects of revascularization surgery, the prevalence of symptoms appeared to be greater than that in the non-MMD population.…”
Section: Discussionmentioning
confidence: 50%
“…Although our study is not directly comparable to the aforementioned survey because of the difference in backgrounds of the populations and the effects of revascularization surgery, the prevalence of symptoms appeared to be greater than that in the non-MMD population. 9 Cerebral hemodynamic impairment likely underlies the symptoms; however, we were not able to attribute the abnormality to the cerebral perfusion measurements. Furthermore, patients who underwent successful revascularization continued to exhibit symptoms years after surgery.…”
Section: Discussionmentioning
confidence: 84%
“…Zahtevi prema adolescentima i očekivanja od njih dolaze iz različitih izvora: roditelja, nastavnika, vršnjaka, ali i njih samih. Ako su zahtevi i očekivanja visoki i adolescenti kontinuirano ulažu velike napore da ih savladaju, to može dovesti do pada energije, zabrinutosti, anksioznosti i stresa (Tanaka, Terashima, Borres, & Thulesius, 2012). Većina studija potvrđuje da hronični i svakodnevni stresori predstavljaju okidače za pojavu negativnih afektivnih odgovora, a lični faktori posebno stabilne osobine ličnosti jesu faktori vulnerabilnosti koji utiču na individualne razlike u verovatnoći javljanja, načinu manifestovanja i prevazilaženju takvih reakcija (Cuffe, McKeown, Addy, & Garrison, 2005;Steinhausen, Haslimeier, & Metzke, 2007;Utsey, Giesbrecht, Hook, & Stanard, 2008).…”
Section: Izvori Stresaunclassified